Electronic Math Problems Analyses and Mastery of Operations, Rules, and Expressions (E-Math Pa More) on the Performance of Grade 9 Students - Samaco, Jenilyn E.; Cabanes, Aileen; Minoza, Joemar T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study sought to assess the effectiveness of Electronic Math Problems Analyses and Mastery of Operations, Rules, and Expressions (e-MATH PA MORE) as digital learning material in the performance of Grade 9 students of Libagon National High School in Math for the School Year 2022-2023. In order to collect data from the students, this study used a two-group quasi-experimental design including pretest and posttest. The study involved the participation of seventy (70) Grade 9 pupils. One of the two sections, each with 35 pupils, acted as the control group, while the other was the experimental group. To determine the study's findings, the data were statistically treated using inferential statistics, specifically T-test (paired and independent), mean and standard deviation, frequency, and percentage. Based on the study's findings, it is possible to infer that both e-Math PA MORE and the traditional style of teaching are effective in teaching Mathematics. However, a greater improvement in Mathematics performance was noticed in the class when e-Math PA MORE was used, indicating that it is more successful than the old method. Hence, e-Math PA MORE offers learning experiences to aid in the formation of knowledge, particularly in mathematics. Furthermore, teachers should be properly equipped with the information and abilities necessary to create e-Math PA MORE. It is recommended that further studies should be conducted to continually improve the utilization of e-Math PA MORE, accentuating on teachers’ preparedness and attitude.